El Pensador y El Censor: Clavijo y Cañuelo - Francisco Sánchez-Blanco (Cuadernos de Ilustración y Romanticismo)
The comparison between the two most important newspapers of the second half of the 18th century helps to specify the idea of what should be understood by the Enlightenment in Spain and to show its continuity and coherence.